Factores socioemocionales que inciden en el rendimiento académico en el área de matemáticas de los estudiantes del subnivel de educación básica superior - Párraga Rendon , Ariel Alexander (2025)
This research analyzes the socio-emotional factors that affect academic performance in mathematics among students in the Upper Basic Education level. Socio-emotional factors consist of elements that either limit or strengthen students’ academic performance in mathematics. The general objective was to analyze the socio-emotional factors that influence the academic performance of students in this subject area. The study was grounded in theories such as Goleman’s Emotional Intelligence, Bandura’s Social Learning Theory, Vygotsky’s Sociocultural Theory, and Gardner’s Logical-Mathematical Intelligence, which emphasize the interaction between emotional and social aspects in learning. The research was developed under the interpretive paradigm, using a qualitative approach and a phenomenological method. Semistructured interviews were conducted with mathematics teachers and educational specialists, whose perceptions were subjected to coding, categorization, and triangulation processes to ensure the validity of the findings. The results revealed that family, social, and emotional contexts are decisive dimensions of academic performance. Anxiety, low self-esteem, and lack of motivation hindered learning, while confidence, empathy, collaborative work, and family support fostered positive performance. Likewise, positive emotions and self-efficacy were found to strengthen students’ commitment and disposition toward mathematics, consolidating meaningful learning. In conclusion, students’ academic performance in mathematics is influenced by the interaction of social and emotional dynamics. Therefore, it is essential to incorporate socio-emotional education into teaching and learning processes to promote emotional well-being and the holistic development of students.